Molecular detection of viral agents in free-ranging and captive neotropical felids in Brazil. (September 2017) - Furtado, Mariana M.; Taniwaki, Sueli A.; de Barros, Iracema N.; Brandão, Paulo E.; Catão-Dias, José L.; Cavalcanti, Sandra; Cullen, Laury; Filoni, Claudia; Jácomo, Anah T. de Almeida; Jorge, Rodrigo S. P.; Silva, Nairléia dos Santos; Silveira, Leandro; et al.
We describe molecular testing for felid alphaherpesvirus 1 (FHV-1), carnivore protoparvovirus 1 (CPPV-1), feline calicivirus (FCV), alphacoronavirus 1 (feline coronavirus [FCoV]), feline leukemia virus (FeLV), feline immunodeficiency virus (FIV), and canine distemper virus (CDV) in whole blood samples of 109 free-ranging and 68 captive neotropical felids from Brazil. Samples from 2 jaguars ( Panthera onca ) and 1 oncilla ( Leopardus tigrinus ) were positive for FHV-1; 2 jaguars, 1 puma ( Puma concolor ), and 1 jaguarundi ( Herpairulus yagouaroundi ) tested positive for CPPV-1; and 1 puma was positive for FIV. Based on comparison of 103 nucleotides of the UL24-UL25 gene, the FHV-1 sequences were 99–100% similar to the FHV-1 strain of domestic cats. Nucleotide sequences of CPPV-1 were closely related to sequences detected in other wild carnivores, comparing 294 nucleotides of the VP1 gene. The FIV nucleotide sequence detected in the free-ranging puma, based on comparison of 444 nucleotides of the pol gene, grouped with other lentiviruses described in pumas, and had 82.4% identity with a free-ranging puma from Yellowstone Park and 79.5% with a captive puma from Brazil. Our data document the circulation of FHV-1, CPPV-1, and FIV in neotropical felids in Brazil.